1984
DOI: 10.1038/310498a0
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent latex microspheres as a retrograde neuronal marker for in vivo and in vitro studies of visual cortex

Abstract: The use of retrograde axonal transport of various substances (for example, enzymes, lectins, synthetic fluorescent compounds) has yielded much information on the organization of neuronal pathways. Each type of retrograde tracer has its own set of attributes which define the scope of problems it can address. We describe here a new class of retrograde tracer, rhodamine-labelled fluorescent latex microspheres (0.02-0.2 micron diameter), which have distinct advantages over other available tracers for in vivo and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
263
1
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 587 publications
(274 citation statements)
references
References 20 publications
8
263
1
2
Order By: Relevance
“…Retrograde tracers were injected into the optic tecta of 3 owls to label neurons in IC. In one owl we used fluorescent latex microspheres (Luma Fluor; Katz et al, 1984), and in 2 others, HRP. For the first method, we first recorded with a metal electrode and located an appropriate injection site in the optic tectum by crudely mapping the visual receptive fields.…”
Section: Methodsmentioning
confidence: 99%
“…Retrograde tracers were injected into the optic tecta of 3 owls to label neurons in IC. In one owl we used fluorescent latex microspheres (Luma Fluor; Katz et al, 1984), and in 2 others, HRP. For the first method, we first recorded with a metal electrode and located an appropriate injection site in the optic tectum by crudely mapping the visual receptive fields.…”
Section: Methodsmentioning
confidence: 99%
“…spheres were used because fibers of passage are not affected such that only direct projections are stained (Katz et al, 1984). Correct placement within the dorsomedial region of the NAc core was verified under 10ϫ magnification using a Cy5 filter to view the bolus of fluosphere injection.…”
Section: Experiments 2: Ascertain Developmental Shifts In D 1 Receptormentioning
confidence: 99%
“…In previous studies on neocortical neurons, for example, the cells either were not identified directly (Foehring and Surmeier 1993;Spain et al 1991) or were identified based on in vitro morphology (Hamill et al 1991), which, as we have shown previously, is not a reliable method for identifying cortical neurons (Giffin et al 1991). To circumvent these difficulties, we have exploited in vivo retrograde labeling to permit the in vitro identification of cortical neurons (Giffin et al 1991;Katz and Iarovici 1990;Katz et al 1984;Solomon et al 1993). In the experiments described here, we have characterized the detailed time-and voltage-dependent properties of the Ca 2+ -independent, depolarizationactivated K + currents in isolated, identified callosal-projecting (CP) neurons from postnatal rat primary visual cortex.…”
Section: Introductionmentioning
confidence: 99%